Uma proposta de desenvolvimento de métricas para a rede da Unipampa - Nascimento, Tiago Belmonte (2013)
One of the biggest challenges in the implementation of the University of Pampa as a public university in the countryside of the state of Rio Grande do Sul is the structure of its data network. Due to its peculiarities, the Unipampa's computer network needs efficient controls to ensure operations with stability and safety. Thus, it ecomes essential to use reliable communication systems that interconnect all these decentralized units. In general, the reliability of communication systems can be improved in three major areas of action. 1) anipulation and encoding of information, 2) improving resources such as power and bandwidth in communication physical channels 3) survey metrics at points of transmission and reception. Aiming to contribute in this process, our research consisted in elaborating a proposal of metric use in the security policy of this network, making the vulnerability detection more efficient as well as the orientation of new policies of safety and investment. The 10 metrics and presented method was used to generate them may be applied in any network with similar characteristics to the network of Unipampa.